(6a-5b+7)+(8a-7b+10)=

Simple and best practice solution for (6a-5b+7)+(8a-7b+10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6a-5b+7)+(8a-7b+10)= equation:


Simplifying
(6a + -5b + 7) + (8a + -7b + 10) = 0

Reorder the terms:
(7 + 6a + -5b) + (8a + -7b + 10) = 0

Remove parenthesis around (7 + 6a + -5b)
7 + 6a + -5b + (8a + -7b + 10) = 0

Reorder the terms:
7 + 6a + -5b + (10 + 8a + -7b) = 0

Remove parenthesis around (10 + 8a + -7b)
7 + 6a + -5b + 10 + 8a + -7b = 0

Reorder the terms:
7 + 10 + 6a + 8a + -5b + -7b = 0

Combine like terms: 7 + 10 = 17
17 + 6a + 8a + -5b + -7b = 0

Combine like terms: 6a + 8a = 14a
17 + 14a + -5b + -7b = 0

Combine like terms: -5b + -7b = -12b
17 + 14a + -12b = 0

Solving
17 + 14a + -12b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + 14a + -17 + -12b = 0 + -17

Reorder the terms:
17 + -17 + 14a + -12b = 0 + -17

Combine like terms: 17 + -17 = 0
0 + 14a + -12b = 0 + -17
14a + -12b = 0 + -17

Combine like terms: 0 + -17 = -17
14a + -12b = -17

Add '12b' to each side of the equation.
14a + -12b + 12b = -17 + 12b

Combine like terms: -12b + 12b = 0
14a + 0 = -17 + 12b
14a = -17 + 12b

Divide each side by '14'.
a = -1.214285714 + 0.8571428571b

Simplifying
a = -1.214285714 + 0.8571428571b

See similar equations:

| 2y=y+y | | -1o=-14v+14 | | x-10=135.950 | | 51=11c-4 | | (-3/x)(x/3) | | 2y=4y-8 | | 5(n+2)=17-2n | | 6u-2=3u-2 | | y=.0155x+.0512 | | 4x-27=3x+13 | | 156=2x-2 | | E-7=6 | | 166=2(6u-1) | | 12x+9=7x+14 | | 8+3d=20 | | 6=6i+6 | | 84=(-24z) | | ln(2)-ln(1)=1 | | 9s-2=8s+4 | | 15-g/320 | | 21y(y+3)= | | (4,2);m=-5/4 | | 8.8y-4=7.7y+7 | | 205=5(6j+5) | | 9x+4y+9z=6 | | logx=-1.175 | | 49-16x=-7 | | 6-x/6 | | 3*(4-y)= | | 2y=y(10/y) | | 32-11x=-7x | | X^5-5x^3-2=0 |

Equations solver categories